EFEKTIVITAS PROGRAM ROMBONG BAZNAS DALAM MENDUKUNG UMKM DI KELURAHAN MEDOKAN AYU KOTA SURABAYA - Fariz Yudhoyono, Mochammad; Khairin Dwi Fitriana, Nur; Fauzan Rais, Farhan; Faldiansyah Ali Putra, Racmat (Education and Talent Development Center of Indonesia, 2025)
The “Surabaya Berdaya” program initiated by the National Zakat Agency (BAZNAS) of Surabaya City is a strategic initiative to support community economic empowerment through productive zakat distribution. One concrete form of the program is the provision of business cart assistance to Micro, Small, and Medium Enterprises (MSMEs) in Medokan Ayu Village, Rungkut District, Surabaya City. This Community Service (PkM) activity aims to evaluate the effectiveness of the cart assistance program in improving the standard of living of mustahik and encouraging their transformation into muzakki. The method used in this PkM is qualitative with data collection techniques through interviews, observations, and documentation. The results of the activity show that cart assistance not only makes it easier for MSMEs to run their businesses, but also contributes to increasing daily income and the entrepreneurial spirit of residents. This program is also supported by ongoing assistance including training in business management, financial management, and product marketing strategies, which significantly strengthens the business capacity of beneficiaries. Testimonials from aid recipients, such as Mrs. Narmi, Mrs. Fitriyah, and Mrs. Joeli, confirmed that the aid had a direct impact on improving welfare, the ability to meet basic needs, and business sustainability. Overall, the BAZNAS cart program has proven effective as an instrument for community economic empowerment based on zakat that has a positive and sustainable impact at the local level.